2022
DOI: 10.3390/nu14050993
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Seattle Sweetened Beverage Tax on the Perceived Healthfulness of Sweetened Beverages

Abstract: Sweetened beverage taxes are associated with significant reductions in the purchase of sweetened beverages. However, it is unclear whether these taxes play a role in shifting perceptions about sweetened beverages and their health impacts. We utilized pre- and post-tax survey data collected from residents in Seattle, WA, a city that implemented a sweetened beverage tax in 2018 and from residents in an untaxed comparison area. We used income-stratified difference-in-difference linear probability models to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
3
2
Order By: Relevance
“…Our results are less consistent with findings from our previous longitudinal cohort study of taxed beverage consumption among lower-income children in Seattle and the nearby nontaxed comparison area . In that study, we found no greater reduction in reported consumption for Seattle children vs those in the comparison area .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are less consistent with findings from our previous longitudinal cohort study of taxed beverage consumption among lower-income children in Seattle and the nearby nontaxed comparison area . In that study, we found no greater reduction in reported consumption for Seattle children vs those in the comparison area .…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are less consistent with findings from our previous longitudinal cohort study of taxed beverage consumption among lower-income children in Seattle and the nearby nontaxed comparison area . In that study, we found no greater reduction in reported consumption for Seattle children vs those in the comparison area . However, dietary consumption is difficult to measure, and multiple studies often have no evidence of decreases in self-reported consumption in places where substantial decreases in sweetened beverage purchasing were seen.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, there was no corresponding decrease in SSB intake directly associated with the tax [64]. Regardless, in the two-year period after the tax was enacted, support for the tax increased among low-income residents [65] and the perceived negative health impacts of SSBs increased among low-income residents [66], which suggests that SSB taxes could have positive spillover effects on the incidence of tooth decay among Seattle children. While no experimental studies have examined whether SSB taxes improve oral health, numerous simulation and model-based studies have predicted the potential public health benefits of a SSB tax on oral health outcomes [67].…”
Section: Plos Onementioning
confidence: 99%
“…Another important factor in the retail stage's prospects in India is the rise in the number of younger runners [15]. In India, large wage packages, nuclear families at metropolitan levels, increasing working-women populations, and growing open entryways inside the organization's stage.…”
Section: Increase In Discretionary Cash Flow and Customer Objectivementioning
confidence: 99%